65‐3: Quantum Dot Light‐emitting Diodes with High Color Purity RGB Cadmium‐Free Quantum Dots. Issue 1 (28th June 2021) - Ryowa, Tatsuya; Sakakibara, Yusuke; Kobashi, Tadashi; Kitano, Keisuke; Ueda, Masaya; Izumi, Makoto; Ogura, Yuko; Michiwaki, Yoko; Nikata, Soichiro; Mishima, Akio; Kalousek, Vit; Takasaki, Mikihiro; et al.
Abstract : This paper reports the highly efficient red, green and blue cadmium‐free quantum dots and light‐emitting diodes (QD‐LED). The red and green cadmium‐free QDs with well optimized structure exhibits high color purity. These new QDs have great potential to be used in next generation QD‐LED display with wide color gamut.